2011
DOI: 10.1002/macp.201100262
|View full text |Cite
|
Sign up to set email alerts
|

Novel Synthesis of Polycarbazole–Gold Nanocomposite

Abstract: A polycarbazole–gold nanocomposite is synthesized based on two polymerization techniques, i.e., emulsion and interfacial using aqueous gold chloride and non‐aqueous carbazole monomer solutions. Use of gold chloride as an oxidant for carbazole not only provides a new chemical synthesis for polycarbazole conducting polymer but also allows the formation of conducting nanocomposite in one simple step. Polymerization of carbazole and further growth of the polymer along with gold nanoparticles are governed by the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 47 publications
1
20
0
Order By: Relevance
“…59,61 However, it was difficult to observe the surface plasmon band of AuNPs in the UV−vis spectrum of the resulting solution ( Figure 5B), even for the one with excess carbazole moieties (molar ratio of HAuCl 4 to carbazoles is 0.4:1). This result is consistent with our previous publication when using carbazole groups functionalized PAMAM dendrimers for the reduction of HAuCl 4 .…”
Section: ■ Results and Discussionmentioning
confidence: 97%
“…59,61 However, it was difficult to observe the surface plasmon band of AuNPs in the UV−vis spectrum of the resulting solution ( Figure 5B), even for the one with excess carbazole moieties (molar ratio of HAuCl 4 to carbazoles is 0.4:1). This result is consistent with our previous publication when using carbazole groups functionalized PAMAM dendrimers for the reduction of HAuCl 4 .…”
Section: ■ Results and Discussionmentioning
confidence: 97%
“…Gupta et al (2011) also reported on the synthesis and properties of polycarbazole-gold nanocomposites. The authors reported that the type of intercalation agent and mixing method had an impact on the structure and properties of the composite materials obtained.…”
Section: Nanocomposites With Engineering Polymersmentioning
confidence: 99%
“…As compared to other conducting polymers, polycarbazoles have a much better stability due to the fully aromatic carbazole moiety [15] as indicated by a higher oxidation potential [16,17]. Carbazole-based conjugated polymer systems are widely known for its photoconductive, hole transport properties and high charge mobility which are essential in developing polymeric light emitting diodes (PLED), organic photorefractive materials, electrochromic displays and other electronic devices [16]. Furthermore, the carbazole moiety is highly reactive at various points: C-2, C-3, C-6, C-7 and the N positions, which allow flexible modification schemes.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the conducting polymer selected is a polycarbazole that has been electrochemically synthesized from a first generation carbazole monomer with tetraethylene glycol functional group. As compared to other conducting polymers, polycarbazoles have a much better stability due to the fully aromatic carbazole moiety [15] as indicated by a higher oxidation potential [16,17]. Carbazole-based conjugated polymer systems are widely known for its photoconductive, hole transport properties and high charge mobility which are essential in developing polymeric light emitting diodes (PLED), organic photorefractive materials, electrochromic displays and other electronic devices [16].…”
Section: Introductionmentioning
confidence: 99%